Microalbuminuria and its associations with clinical profile and complications of type 2 Diabetes Mellitus - Shrestha, Sanjay; Mandal, Rajesh Kumar; Maharjan, Kijan (Journal of Advances in Internal Medicine, 2021)
Background and Aims: Microalbuminuria is an early marker of diabetic nephropathy, which accounts for a significant reduction in life expectancy of diabetic patients. Timely detection of microalbuminuria facilitates appropriate preventive and therapeutic approaches to minimize risks. The aim of this study is to determine the prevalence and association of microalbuminuria with clinical profile and complications of type 2 diabetes mellitus. Methods: This study was a descriptive, cross sectional study involving 100 diabetic subjects between July 2018 to January 2019 at Bir Hospital. Microalbuminuria (mg/dl) was defined as spot urine albumin to creatinine ratio of 30-300 mg/g (Kidney Disease Improving Global Outcomes guidelines) in a single spot urine sample. Statistical analysis was done using Statistical package for the social sciences version 20. Results: Microalbuminuria was found in 35% of the sample and the rate was significantly higher among males (P =0.027). Microalbuminuria was significantly related to Body mass index (P = 0.018), duration of diabetes (P =0.000), retinopathy (P = 0.000) and stroke (P = 0.043). No statistically significant relation was found between microalbuminuria and age (P = 0.366), hypertension (P = 0.208), HbA1c (P = 0.098), dyslipidemia (P = 0.171) and ischemic heart disease (P = 0.651). Conclusions: This study shows high prevalence of microalbuminuria in Nepalese Type 2 diabetes mellitus. Screening for microalbuminuria should be done for all the type 2 diabetes mellitus patients for early detection and management of complications of diabetes mellitus.